Aspek Pedagogis Kisah Penyembelihan Nabi Ismail AS dalam Perspektif Tafsīr Mauḋū’i Abdul Karim Zaidan - Khofifah, Nur; Fawaid, Achmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study attempts to explore the story of Prophet Ibrahim and Prophet Ismail as pedagogical education figures based on Abdul Karim Zaidan's perspective. The main focus of this study is on the pedagogical methods and educational values of the story of prophet Ismail's slaughter. By using the analysis of Tafsir Maudhu'i and a narrative approach with the primary source of the book al -Mûstãfãd Mîn Qãsãs al-Qur'ãn Surah Ash-Shaffat: 99-111. The values of Islamic education in Abdul Karim Zaidan's pedagogy include methods of instruction, dialogue, modeling, and the material of obedience and purity, courtesy, and sincerity. Thus, the study results that the first aims of education are: humanization, the formation of insan Kamil, and moral development. Second, the educational values as a guide for parents in Abdul Karim Zaidan's perspective education are: 1) Subject to Allah's Commands, 2) Good examples for Muslim youth and children, 3) Obedience to Allah's commands, 4) Allah's temptation to his faithful servants, 5) Islamic morals, and 6) Fulfilment of family rights.